A comparison of cylindrical and Inoue balloon techniques for mitral valvotomy in patients in the United Kingdom. Issue 5 (November 1994) - Shaw, T R; Turnbull, C M; Currie, P; Flapan, A D; Pringle, S; Lee, B C
Abstract : OBJECTIVES--To compare the use of cylindrical balloons and the Inoue balloon for percutaneous mitral valvotomy in patients in the United Kingdom. DESIGN--Comparison of the haemodynamic results, complications, and symptomatic outcome of balloon dilatation for mitral stenosis in consecutive patients treated by cylindrical balloons and a second consecutive series of patients treated by the Inoue balloon. SETTING--A tertiary cardiac referral centre in Scotland. PATIENTS--70 patients (mean age 60.6 years) treated by the single or double cylindrical balloon technique and 70 patients (mean age 58.9 years) treated with the Inoue balloon method. MAIN OUTCOME MEASURES--Success in obtaining dilatation at the mitral orifice, procedure and screening times, increase in valve area, complications, and early symptomatic outcome. RESULTS--Dilatation of the mitral valve was obtained in 91% of patients when cylindrical balloons were used and in 99% of patients treated with the Inoue balloon. Use of the Inoue balloon gave significantly shorter procedure and screening times. Technical problems in obtaining and maintaining the position at the mitral orifice were more common with cylindrical balloons. Improvements in valve area and symptoms were not significantly different with use of the two types of balloon. The Inoue balloon avoided cardiac tamponade and the creation of larger atrial septal defects, but had a higher incidence of increase in mitral reflux. CONCLUSIONS--In these elderly patients, the Inoue balloon method was safer and faster for percutaneous mitral valvotomy, with a higher success rate for dilatation within the valve orifice. Haemodynamic and symptomatic improvement was similar with the two techniques.